Incoterms: Reconstructing International Sales Contracts in Harmony with Sharia Economic Law - Arif, Junaidi; Parmitasari, Indah; Sutrisno, Nandang (Sekolah Tinggi Agama islam Negeri Majene, 2025)
In global trade, Incoterms play an essential role as a standardised framework that defines the allocation of responsibilities and risks between sellers and buyers. However, from the perspective of Sharia economic law, the application of Incoterms in some instances has the potential to create gharar, which can impact the validity of the agreement. This study aims to analyse the gap between the provisions of Incoterms 2020 and the principles of fiqh muamalah, particularly in terms of responsibility sharing and risk transfer in international sales contracts. This research searched various academic databases, applying pre-established criteria to obtain relevant studies for review. These studies were further strengthened by normative juridical analysis based on jurisprudence literature and Islamic legal doctrines. A discrepancy between the provision of Incoterms 2020 and the principles of fiqh muamalah, especially concerning risk transfer clauses (such as FOB and CIF). This alignment carries the potential to lead gharar into contractual agreements. Ambiguity in the division of responsibilities can create situations conflicting with the core Islamic principles of ‘adl (justice) and shaffafiyyah (transparency). Consequently, there is a compelling need to reform international contractual systems to integrate Sharia principles while still accommodating the practical demands of global trade. The finding of this study provides a basis for formulating a more transparent and fairer contractual framework by integrating Sharia principles so that gharar can be prevented, leading to maṣlaḥah (public welfare) within cross-border transactions.